Aesthetic results in post-surgical nasal defects regenerated with autologous platelet- and leukocyte-rich fibrin - Leodanyi Adán Socarrás; Tairí Borges García; Manuel Antonio Arce González; Alba María Díaz Suárez; Carmen Rosa Cantero Marín (Editorial Ciencias Médicas, 2022)
Introduction: In the reconstruction of nasal skin defects, several techniques have been used worldwide. Innovative practices use platelet concentrates for their modulating properties and favoring tissue regeneration. Objective: Determine the aesthetic results associated with the use of autologous fibrin rich in platelets and leukocytes, for the regeneration of post-surgical nasal skin defects. Methods: A quasi-experimental, longitudinal and prospective study was conducted in the Maxillofacial Surgery Service of "Arnaldo Milián Castro" University Hospital in the city of Santa Clara, Villa Clara province, Cuba, from September 2015 to June 2019. An intentional, non-probabilistic sampling of 31 patients was carried out. From a blood donation from the patient, a fibrin membrane rich in platelets and leukocytes was obtained, which was sutured in the post-surgical nasal defect. Variables such as the aesthetic result were studied, evaluated on the basis of parameters such as elasticity, color, volume and surface. Results: The mean age was 62.71 ± 11.09 years and 61.29% of the sample corresponded to the male sex. A good aesthetic result was shown by 90.32% of the patients, which was significantly associated with the degree of epithelialization. Conclusions: A good aesthetic result was obtained in patients where the fibrin membrane rich in leukocytes and autologous platelets was used, regardless of the presence of diabetes mellitus and toxic habits. The aesthetic result was significantly associated with the degree of epithelialization and age.